Determination of protonation constants and structural correlations for some tertiary formamides and acetamides in sulfuric acid with UV spectroscopy - Stojković, Goran; Dimitrieska-Stojković, Elizabeta; Popovski, Emil (Society of Chemists and Technologists of Macedonia, 2015)
The protonation of ten aliphatic amides in sulfuric acid media was studied by UV spectroscopy. The pKBH+ values and solvation parameters were calculated using Yates and McClelland Method, Excess Acidity Method and Bunnett and Olsen Method. pKBH+ values were –1.44, –1.15, –0.80, –0.32, –1.13 and –0.80 for formamide, dimethylformamide, diethylformamide, diisopropylformamide, diisobutylformamide and dibutylformamide, respectively. According to the pKBH+ values obtained for acetamide, dimethylacetamide, diethylacetamide and diisopropylacetamide (–0.57, –0.29, –0.32 and 0.36, respectively), analogous acetamides were more basic than formamides. Applying the Hammett’s equation, satisfactory correlation could be gained only for some formamides, the basicities of which increased linearly with the inductive effect of the electron donating groups. From Taft’s approach, it can be concluded that the polar effect slightly dominates over the steric one. Excellent correlation between pKBH+ and solvation parameters m* was achieved for formamide, dimethylformamide and diethylformamide. At half- and full-protonation, better correlation was obtained for formamides than for acetamides.